Heavy metal pollution assessment in marine sediments in the Northwest coast of Sabah, Malaysia - Sin-Yi Ling; Asis Junaidi; Abdullah Mohd-Harun; Musta Baba (China Geology)
Heavy metal contents along the Northwest coast of Sabah were determined to interpret the pollution level in the marine sediment. The metal abundance is regulated by the physico-chemical properties such as the average sediment pH (7.82, 9.00 and 8.99), organic matter (0.62%, 1.60%, and 2.27%), moisture content (25.00%, 29.70%, and 15.00%) and sandy texture in Kota Belud, Kudat and Mantanani Island, respectively. The major elements show Ca>Fe>Mg>Al>Mn for all study sites, while the heavy metals show Ni>Cr>Zn>Cu>Co>Pb, Cr>Ni>Zn>Cu>Pb>Co and Zn>Pb>Cr>Ni, for Kota Belud, Kudat and Mantanani Island, respectively. The pollution degree of heavy metals was evaluated by using the Sediment Quality Assessment (SQA). The SQA parameters indicated none to moderate pollution in Kota Belud that shows Class 0, Class 1 and Class 2 pollution. The parameters also indicated none to low pollution in Kudat and Mantanani Island that show only Class 0 pollution. The enrichment factor (EF) suggested minor to moderately severe metal enrichment by anthropogenic sources in Kota Belud, whereas only minor enrichment in Kudat and Mantanani Island. The modified pollution degree (MCD<1.5) and pollution load index (0 ⩽ PLI<1) indicating only low pollution level in the marine sediments for all study sites. The objectives of this study are: (1) to determine the physico-chemical parameters of sediments, (2) interpret the heavy metal contents and (3) evaluate the sediment quality.©2023 China Geology Editorial Office.